Fluid-structure interaction analysis of a patient-specific right coronary artery with physiological velocity and pressure waveforms - Torii, Ryo; Wood, Nigel B.; Hadjiloizou, Nearchos; Dowsey, Andrew W.; Wright, Andrew R.; Hughes, Alun D.; Davies, Justin; Francis, Darrel P.; Mayet, Jamil; Yang, Guang-Zhong; Thom, Simon A. McG; Xu, X. Yun (Communications in numerical methods in engineering, 2009)
Coupled fluid–structure interaction (FSI) analysis of the human right coronary artery (RCA) has been carried out to investigate the effects of wall compliance on coronary hemodynamics. A 3‐D model of a stenosed RCA was reconstructed based on multislice computerized tomography images. A velocity waveform in the proximal RCA and a pressure waveform in the distal RCA of a patient with a severe stenosis were acquired with a catheter delivered wire probe and applied as boundary conditions. The arterial wall was modeled as a Mooney–Rivlin hyperelastic material. The predicted maximum wall displacement (3.85 mm) was comparable with the vessel diameter (∼4 mm), but the diameter variation was much smaller, 0.134 mm at the stenosis and 0.486 mm in the distal region. Comparison of the computational results between the FSI and rigid‐wall models showed that the instantaneous wall shear stress (WSS) distributions were affected by diameter variation in the arterial wall; increasing systolic blood pressure dilated the vessel and consequently lowered WSS, whereas the opposite occurred when pressure started to decrease. However, the effects of wall compliance on time‐averaged WSS (TAWSS) and oscillatory shear index (OSI) were insignificant (4.5 and 2.7% difference in maximum TAWSS and OSI, respectively). Copyright © 2009 John Wiley & Sons, Ltd.